2011
DOI: 10.1016/j.brat.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Believe in yourself: Manipulating beliefs about memory causes checking

Abstract: One of the most common compulsions in obsessive-compulsive disorder (OCD) is repeated checking. Although individuals often report that they check to become more certain, checking has been shown to have the opposite effect - increased checking causes increased uncertainty. However, checking may also be thought of as beginning because of memory uncertainty. Beliefs about responsibility, over-estimation of threat, intolerance of uncertainty, perfectionism, and importance of and control of thoughts are already kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…Thus, while previous research showed that patients with OCD in general perform more checking behavior than healthy controls (Jaafari et al, 2013;Kim, Roh, Kim, & Cha, 2012), and that uncertainty induces greater urges to check (Alcolado & Radomsky, 2011), the present study combined these findings. It showed that yet mild uncertainty, unrelated to obsessions, promotes actual checking behavior in OCþ but not OC À individuals.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, while previous research showed that patients with OCD in general perform more checking behavior than healthy controls (Jaafari et al, 2013;Kim, Roh, Kim, & Cha, 2012), and that uncertainty induces greater urges to check (Alcolado & Radomsky, 2011), the present study combined these findings. It showed that yet mild uncertainty, unrelated to obsessions, promotes actual checking behavior in OCþ but not OC À individuals.…”
Section: Discussionsupporting
confidence: 55%
“…While it may seem intuitive Bulletin of the Menninger Clinic that doubt about completing a task begets checking-a direction supported by some research (e.g., Cougle, Salkovskis, & Wahl, 2007;Nedeljkovic, Moulding, Kyrios, & Doron, 2009)-some experimental studies have demonstrated the opposite direction, namely that checking elicits doubt about completing tasks as characterized by decreases in memory confidence (Alcolado & Radomsky, 2011;Boschen & Vuksanovic, 2007;van den Hout & Kindt, 2003). Thus, the relationship between DA and checking symptoms may be reciprocal, and prospective studies of individuals with OCD that take particular care to measure memory confidence may provide more insight into the cause-and-effect patterns of these entwined constructs.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, experimental manipulations have consistently shown the direct impact of responsibility on checking (e.g., Arntz et al, 2007;Ladouceur et al, 1995;Lopatka & Rachman, 1995), making responsibility beliefs a fundamental component of the theory and a core target in CBT for OCD (e.g., Clark, 2004;Rachman, 2003). Recent experimental work has also provided support for the expansion of cognitive theory (e.g., Alcolado & Radomsky, 2011;Gagné & Radomsky, 2017) and for contemporary formulations of obsessions and compulsions (e.g., Lazarov et al, 2010), indicating that CBT for OCD is steadily expanding.…”
Section: Discussionmentioning
confidence: 99%
“…These beliefs include inflated responsibility, threat overestimation, intolerance for uncertainty, perfectionism, overimportance of thoughts, and beliefs about the need to control one's thoughts (e.g., Obsessive Compulsive Cognitions Working Group [OCCWG], 1997[OCCWG], , 2005. Other lines of research have proposed that metacognition, such as confidence in one's attention and perception (e.g., Hermans et al, 2008) and negative beliefs about memory (e.g., Alcolado & Radomsky, 2011), also plays a role in the development and maintenance of symptoms. Recent work further suggests that negative beliefs about losing control over one's thoughts and behavior should also be considered in cognitive models of OCD (Gagné & Radomsky, 2017).…”
Section: Cognitive Modelsmentioning
confidence: 99%